Effects of the menstrual cycle on anterior cruciate ligament injury risk - A systematic review - Hewett, T. E.; Zazulak, B. T.; Myer, G. D. (The American Journal of Sports Medicine, 2007)
Several theories have been proposed to explain the 3- to 6-fold gender difference in the incidence of anterior cruciate ligament injuries. One potential theory for the increased incidence is based on gender-related hormonal differences between men and women, especially after puberty and the onset of menses in the female athlete. The purpose of this systematic review was to compile and systematically analyze the published literature to determine if the menstrual cycle is associated with anterior cruciate ligament injury risk and to provide an objective comparison of the published results. Investigations were included in the systematic review if the report included associations between the menstrual cycle and noncontact anterior cruciate ligament injuries in female athletes. Abstracts and unpublished studies were excluded. Seven articles were identified that met the systematic review inclusion criteria. The 7 reviewed studies favored an effect of the first half, or preovulatory phase, of the menstrual cycle for increased anterior cruciate ligament injuries. The 6 studies that separated the non-oral contraceptive and oral contraceptive data also favored an effect of the first half of the menstrual cycle for increased anterior cruciate ligament injuries. The clinical relevance of this finding is that female athletes may be more predisposed to anterior cruciate ligament injuries during the preovulatory phase of the menstrual cycle. These findings may lead to potential interventions targeted toward this phase of the menstrual cycle to reduce the incidence of anterior cruciate ligament injury.